Cost of prescribed NSAID-related gastrointestinal adverse events in elderly patients - Rahme, Elham (Blackwell Science Inc, 2001)
AIMS: It is well established that nonsteroidal anti-inflammatory drugs (NSAIDs) have gastrointestinal (GI) side-effects. However, the cost of health care resources spent on preventing and managing these side-effects is not clear. The objective of this study was to estimate the direct cost of NSAID-related GI events in an elderly population. METHODS: From the Régie de l'assurance-maladie du Québec (RAMQ) database, we obtained medical, pharmaceutical and demographic records of a 10% random sample (n = 49 033) of seniors who, between January 1, 1993 and December 31, 1997, had a dispensed prescription of a NSAID. Patients who did not have any GI events during the year prior to their first dispensed prescription were included in the cohort. All patients were followed-up for 2 years. The daily direct Canadian dollar costs of GI events that were incurred by these patients while they were on NSAID therapy were compared with those of GI events that were incurred by these same patients while they were not on NSAID therapy. The difference in these daily costs was attributed to NSAIDs. RESULTS: A total of 12 082 new NSAID users were included in the study. Two hundred and seventeen (1.8%) were hospitalized for GI-related problems; of these, 130 (60%) had their GI hospitalization as their first GI event; 3257 (27.0%) used gastroprotective agents (GPAs), and 857 (26.3%) took GPAs without any apparent prior GI symptoms; 801 (6.6%) had GI diagnostic tests; and 661 (5.5%) died. The average direct costs of GI side-effects per patient-day on NSAIDs were 3.5 times higher than those of a patient-day not on NSAIDs. The direct cost of GI side-effects per patient-day on NSAIDs was $1.34, of which more than 70% ($0.94) was attributed to GI events resulting from NSAID treatment. CONCLUSIONS: Approximately one Canadian dollar was added to patient costs for every day he/she was on NSAID therapy. Safer therapies and appropriate patient risk management may potentially reduce NSAID-related health care resource use.